Rosetta Stone Application on Students’ Pronunciation - Hermana, Rifqi Naufal (Journal of English Teaching and Linguistics Studies (JET Li), 2023)
Expressing an idea or explaining something was needed to pay attention to English pronunciation. There are many digital platforms for learning English, especially for practicing pronunciation. Rosetta Stone is a unique language-learning application that makes it easy for students to learn because it is flexible. The aim of this research is to find out whether there is a difference in the influence of the use of Rosetta Stone Application and PowerPoint media on students' pronunciation. This research was conducted at SMA Negeri 1 Parungkuda. The researcher used a Quasi Experimental design for this research. The researcher involved students of class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. The research instrument was an oral test to measure the influence of students' pronunciation on vowels, especially diphthongs with a total of 20 oral questions were used as research instruments. Data was collected through pre-test and post-test and were analyzed using the t-test with SPSS 22. The results of the independent t-test calculation showed a t-test value of 2,100, while the t-table is 1,9954 at a significance level of 0.05 and the degrees of freedom (df) is 68. The t-count is higher than the t-table (2,100 1,9954). It means that there was a difference in the influence of the use of Rosetta Stone Application and PowerPoint media. The different that distinguishes the experimental and control groups is the result of the final scores of the two classes, in which the experimental group has higher scores than the control group. In conclusion, the results between the experimental group and the control group have a significant difference.